Metabolites Identification of Curcumin, Demethoxycurcumin and Bisdemethoxycurcumin in Rats After Oral Administration of Nanoparticle Formulations by Liquid Chromatography Coupled with Mass Spectrometry - Li, Rui; Wang, Qi; Fan, Jing-Ran; He, Jun-Bin; Qiao, Xue; Xiang, Cheng; Guo, De-An; Ye, Min (World Journal of Traditional Chinese Medicine, 2016)
Background: Curcuminoids are promising cancer chemopreventive agents. Curcumin, demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC) are the major bioactive curcuminoids in turmeric. However, comprehensive metabolic studies of these three curcuminoids are still limited.